EFL Learner Autonomy at a Pondok Pesantren in South Kalimantan, Indonesia: A Narrative Inquiry - Abin, Najmi Jailani; Pratiwi, Widya Rizky; Sujiatmoko, Ahmad Heki (Journal Corner of Education, Linguistics, and Literature, 2026)
This study explores how learner autonomy is experienced by students learning English as a foreign language in a highly structured Pondok Pesantren. The study aims to describe the types of learner autonomy demonstrated by students through their learning experiences. This research employed a narrative inquiry approach. This approach is particularly suitable for the Pondok Pesantren context as it captures students’ lived experiences and how learner autonomy is negotiated within a highly structured, faith-based educational environment. Five Grade XI students aged 16-17 years from a Pondok Pesantren in South Kalimantan, Indonesia, were purposively selected based on their active participation in English learning and the uniqueness of their learning experiences. Data were collected through in-depth interviews, classroom and out-of-class observations, and document analysis. The data were analyzed using narrative thematic analysis. The findings show that students demonstrated several types of learner autonomy, including technical, psychological, sociocultural, proactive, reactive, political, and critical autonomy. These forms of autonomy appeared in daily learning activities such as using dictionaries and limited digital tools, interacting with peers, completing teacher-guided tasks, and initiating learning activities independently. However, autonomy related to learning decision-making and critical reflection was less visible and appeared within the boundaries of institutional routines and learning practices in the Pondok Pesantren context. Conceptually, the study highlights learner autonomy as a contextual and evolving process shaped by institutional structures and students’ lived experiences. The study concludes that learner autonomy in a Pondok Pesantren develops gradually as a contextual and evolving process reflected in students’ everyday English learning experiences.